A Review: Depolymerization of Lignin to Generate High-Value Bio-Products: Opportunities, Challenges, and Prospects - Zhou, Ningning; Thilakarathna, W. P. D. Wass; He, Quan Sophia; Rupasinghe, H. P. Vasantha (Frontiers in energy research, 2022)
Lignin is identified as a promising candidate in renewable energy and bioproduct manufacturing due to its high abundance, polymeric structure, and biochemical properties of monomers. Thus, emerging opportunities exist in generating high-value small molecules from lignin through depolymerization. This review aims at providing an overview of the major technologies of lignin depolymerization. The feasibility of large-scale implementation of these technologies, including thermal, biological, and chemical depolymerizations, are discussed in relation to potential industrial applications. Lignin as a renewable alternative to petroleum-based chemicals has been well documented. This review attempts to emphasize potential applications of lignin-derived monomers and their derivatives as bioactives in food, natural health product, and pharmaceutical sectors. The critical review of the prospects and challenges of lignin-derived bioproducts reveals that the advancement of research and development is required to explore the applications of depolymerization of lignins to their full potential.